Research on the pavement performance of lignin fiber toughened foam asphalt cold recycled mixes - Zhang, Min; Zhao, Yanan; Wang, Chenxi; Jin, Duo; Chen, Qi (Frontiers in Built Environment, 2025)
To improve the pavement performance and toughness of foam asphalt cold recycled mixture (FACRM), the effects of lignin fiber on the pavement performance of FACRM at 0%, 0.3%, 0.6% and 0.9% dosages (relative to foam asphalt cold recycled mixtures) were investigated. The influence of different fiber dosages on the performance of FACRM was investigated through the high-temperature rutting, semi-circular bending, and freeze-thaw splitting tests, and the microscopic morphology of the fiber on the FACRM damage interface was observed by scanning electron microscope (SEM). The results show that with the increase in lignin fiber dosage, the maximum dry density of FACRM shows a decreasing trend; the optimum moisture content and the optimum asphalt content gradually increase; dynamic stability, fracture energy, and tensile strength ratio (TSR) show a pattern of change that first increases and then decreases. The fiber enhancement mechanism of FACRM pavement performance is that its dispersion as a bridge in the mixture to form a three-dimensional network structure provides the reinforcement. The recommended dosage is 0.3% based on a comprehensive review of the effects of lignin fiber on the recycled mixture pavement performance and microscopic morphology of the results.